OPTICAL SIGNAL PROCESSING FROM OBSERVED OBJECTS THE METHOD OF THE LEAST SQUARE PONY WITH WEIGHING OBSERVATIONS - V. G. Andrejev; D. V. Avramenko (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2019)
This paper describes the implementation of a technique to improve the accuracy of spectral evaluation of periodic changes in the brightness of multi-frequency reflections from space objects under conditions of a smooth change in their intensity. A comparative analysis is carried out to determine the relative deviation of the estimate of the rotational speed ΔF by the classical method of the smallest squares of the Proni and weighing observations.